Supplementation of Lipoic Acid, Zinc and Clopidogrel Reduces Mortality Rate and Incidence of Ventricular Arrhythmia in Experimental Myocardial Infarction - Abdel-Hady, Enas; Mohamed, Fatma; Ahmed, Mona; Abdel-Salam, Mohamed; Ayobe, Mahmoud (Frontiers in Physiology, 2021)
Despite the significant advances in management of coronary heart diseases, myocardial infarction (MI) is still associated with a high mortality rate. The present study was planned to investigate the possible protective effects of the anti-oxidants lipoic acid and zinc sulphate as well as the anti-platelet clopidogrel on cardiac dysfunction in experimental isoproterenol (ISO)-induced MI, aiming at achieving useful means for protection and therapy against MI. Wistar rats of both sexes were allocated into five groups: control, untreated MI and MI pre-treated with lipoic acid, zinc, or clopidogrel. All rats were subjected to ECG recording and measurement of plasma levels of troponin I, creatine kinase-MB (CK-MB) unit, triglycerides and total cholesterol. The hearts were isolated and studied on Langendorff preparation for assessment of intrinsic cardiac activities. The results revealed that the percent mortality was markedly reduced upon pre-treatment and the total arrhythmia was also decreased except for the zinc pre-treated rats. The ST-segment elevation was significantly reduced and the plasma levels of CK-MB were only decreased in lipoic acid and clopidogrel pre-treated rats with variable hypolipidemic effect. Hearts of clopidogrel pre-treated rats showed augmented inotropic activity both basal and in response to -adrenergic stimulation. While zinc pre-treated hearts revealed improved rate of contraction and increased myocardial flow rate. Overall, these results indicate that lipoic acid, zinc and clopidogrel were variably effective in modifying the ISO-induced MI insults and offered partial protection against experimental myocardial damage.